The Value of sharing : the story of the Mayo brothers - Johnson, Spencer (La Jolla, CA : Value Comm., Inc. Pub, 1978)
The Mayo brothers, knowing the importance of sharing, enter a career in which they can share their knowledge and skills, and money with sick people and other doctors.
Keywords: May, Charles Horace, 1865-1939; Mayo, William James, 1861-1939; Sharing; Surgeon--Minnesota--Rochester--Biography; Physicians